PEDAGOGICAL CONDITIONS FOR THE PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN SOCIONOMIC PROFESSIONS FOR HEALTH-PRESERVING ACTIVITIES (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the pedagogical conditions for the professional training of future professionals in socionomic professions for health-preserving activities. The relevance of this issue in the modern educational space is highlighted, driven by the need to develop students' life skills aimed at maintaining and strengthening the physical, mental, and social health of young people. An analysis of scientific approaches to the definition of the concept of "pedagogical condition" is carried out, emphasizing the importance of interdisciplinary integration of knowledge from medical, psychological, and pedagogical disciplines to ensure a comprehensive approach to the professional training of future specialists. The main focus is placed on such pedagogical conditions as: the integration of theoretical knowledge and practical skills, the development of motivational and value-based attitudes towards health preservation, the use of modern digital technologies for monitoring students' physical health, and the creation of a supportive psychological and pedagogical environment for the formation of health-preserving competence. The importance of developing students' abilities for reflection, self-assessment, and self-control as essential components of professional readiness for work in educational institutions is emphasized. The article outlines the prospects for further research aimed at developing innovative teaching methods, creating integrated educational programs, and implementing social initiatives to support student health. The article is intended for educators, researchers, students of socionomic professions, and practical specialists interested in physical education, health preservation, and improving the quality of professional education.
Keywords: professional training; socionomic professionals; health-preserving activities; pedagogical conditions for professional training of future socionomic professionals for health-preserving activities; health-preserving competence; motivational and value-based attitude towards health preservation